PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA APARATUR PEMERINTAH (STUDI KASUS DI KANTOR CAMAT SAPE KABUPATEN BIMA NTB) - Imran Imran; Agus Widarko (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACT The effect is a norm leadership did someone by the people like giving something for the other people (Suranta in Regina 2010: 15). Sometimes the leader has a style to leadership which the different for one and the others. Leadership is a purpose for influence and direct behavior subordinate or other people for getting purpose by organization. The leaders who give good motivation and understand to subordinate will give a effect to their a jobs. Various the leadership of which is used in organization by leader and then can help get positive effect in a jobs for subordinate or subordinate performance especially, their will more motivation in perform a jobs and obligation agree with regulation and assignment for get point of view and mission organization. The data involve the use of research is data primer which getting by respondent used quesener of already experiment validity and reliability. Was 67 respondents choose was sample by subordinate Sub district office. The data analyze by analyses regrets double linear. Result by research was is leadership and motivation giving effect performance apparatus leader at sub district office at Sape-Bima of NTB. This case agree with the leaders character, like attitude, fair, giving suggestion or included, support for purpose, expression result, get positive condition, clearly for all the problem, can clearly the problem in organization, well a spirit for subordinate and appreciative. In addition motivation like filling for jobs, fair a wage, a good circle, appreciation for a jobs and leaders must be a good attitude. Key word: Leadership, Motivation and performance